Arthroscopic Management for Stiff Elbow - Micic, Ivan; Jeon, In Ho; Kang, Dong Ho; Hong, Han Pyo; Baqays, Abdullah; Stojiljković, Predrag; Jung, Hong Jun (Acta medicae Medianae, 2021)
Stiff elbow is common clinical consequence in elbow joint. Impairments in active daily living is noted in flexion-extension stiffness as well as rotational stiffness. Elbow stiffness can be divided into 3 different types: Intrinsic, Extrinsic and mixed types. Intrinsic type is referred to as articular deficit and loss of conformity resulting from trauma, infection or arthritic changes of intra-articular origin. Extrinsic stiffness is caused by fibrotic changes or scar formation of surrounding muscles , ligaments or skin. Ectopic ossification is a typical example of extrinsic type of stiff elbow. Mixed type is defined when both intrinsic cause and extrinsic causes are combined, and is most common among post-traumatic elbow stiffness. Arthroscopic release of anterior capsule for flexion contracture can be done in safe way. In cases of severe joint contracture, however, it is safe to release and isolate ulnar nerve with minimal incision before arthroscopic capsular release; otherwise sudden gain of flexion after extensive release of the capsule may tether ulnar nerve around posterior aspect of medial epicondyle. Recent trend of arthroscopy is to draw equal clinical outcomes compared to existing open surgery by incising minimally and starting early rehabilitation to lessen patients’ pain and achieve better range of motion. But a thoughtful understanding of elbow anatomy and skillful arthroscopic technique is essential to minimize neurovascular insult or other surgical complication caused by inexperience.